Wage differentials, fairness and social comparison: an experimental study of the co-employment of permanent and temporary agency workers - Dorothea Alewell; Andreas Nicklisch (Max Planck Institute for Research on Collective Goods, 2006)
Recent experimental literature in labor economics shows that fairness concerns make a substantial difference for working decisions. Our study systematically explores how the existence of multiple fairness foci influences wage setting and acceptance thresholds. Particularly, we focus on the effect of horizontal fairness concerns, i.e., the wage comparison among employees. For our experiment, we use an institutional design of wage negotiations among employers, employees and temporary agency workers. Working agencies hire these workers and rent them out to firms. Thereby, we create a heterogeneous background of the labour force. Although temporary agency workers do the same work, typically, they receive lower wages due to the intermediate agency. The results of our laboratory experiments indicate that the availability of information concerning co-employees wage offers strongly influences the wage set and participants acceptance of contracts. Whereas the relation of average wages is not influenced by the order of the decisions, the absolute level of wages is dependent on the decisions. We find that temporary agency workers who decide on a wage offer after permanent employees receive a premium in addition to their wages, while permanent employees take a cut in wages if they get their wage offer after temporary workers have decided on their offers. These results are more influenced by self-regarding social comparison preferences than by other-regarding horizontal fairness concerns.
Keywords: C92; J33; M12; M52; 330; Experimental economics; horizontal fairness norms; labour economics; social preferences; vertical fairness norms